Porosity of closed carbon nanotubes compressed using hydraulic pressure - Gauden, P.; Terzyk, A.; Furmaniak, S.; Wisniewski, M.; Kowalczyk, Piotr; Bielicka, A.; Zielinski, W. (Springer New York LLC, 2013)
Experimental data of nitrogen adsorption (T = 77.3 K) from gaseous phase measured on commercial closed carbon nanotubes are presented. Additionally, we show the results of N2 adsorption on compressed (using hydraulic press) CNTs. In order to explain the experimental observations the results of GCMC simulations of N2 adsorption on isolated or bundled multi-walled closed nanotubes (four models of bundles) are discussed. We show that the changes of the experimental adsorption isotherms are related to the compression of the investigated adsorbents. They are qualitatively similar to the theoretical observations. Taking into account all results it is concluded that in the "architecture" of nanotubes very important role has been played by isolated nanotubes.